Comparative Analysis of Neural Network Architectures for Predicting Chronic Disease Indicators Using CDC’s Chronic Disease Indicators Dataset - Airlangga, Gregorius (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
This research evaluates the performance of three machine learning models—Neural Network (NN), Convolutional Neural Network (CNN), and Recurrent Neural Network (RNN) using Long Short-Term Memory (LSTM) units—in predicting chronic disease indicators using the CDC's Chronic Disease Indicators (CDI) dataset. The study employs a comprehensive preprocessing pipeline and 5-fold cross-validation to ensure robustness and generalizability of the results. The CNN model outperformed both the NN and RNN models across all key performance metrics, achieving an accuracy of 0.6303, precision of 0.6445, recall of 0.6303, and F1 score of 0.5950. The superior performance of the CNN is attributed to its ability to capture spatial hierarchies and interactions within the structured dataset. The findings underscore the importance of selecting appropriate machine learning architectures based on the data characteristics. This research provides valuable insights for public health officials and policymakers to enhance chronic disease monitoring, early detection, and intervention strategies. Future work will explore hybrid models and advanced techniques to further improve predictive performance. This study highlights the potential of CNNs in public health informatics and sets a foundation for further research in this domain